Sistem penilaian kualiti e-servis di Perpustakaan Sultanah Zanariah (PSZ) UTM, Skudai - Abu Bakar, Noor Suriana (2005)
E-service quality assessment is a very important factor for Perpustakaan Sultanah Zanariah (PSZ). This research is conducted for the purpose of toolkit assessment development, which shall help users to conduct the quality assessment effectively. This toolkit assessment will be used to enforce competitive environment between e-service PSZ suppliers with other universities. It is also to improve the e-services quality which will deliver to the users. E-services supplies also will enhance the e-services quality from the feedback given by the users. Besides that, e-services quality assessment will give satisfaction to the users especially students and PSZ staff. Hence with this method, it will support e-service PSZ’s supplier to enhance the e-services quality in the future